Dynamics of cavitation in a Douglas-fir tree-ring: transition-wood, the lord of the ring? - Dalla Salda, Guillermina; Fernandez, María Elena; Sergent, Anne Sophie; Rozenberg, Philippe; Badel, Eric; Martinez Meier, Alejandro (INRA, 2020)
The objective of this work wa s to investigate the dynamics of embolism formation within a Douglas fir tree ring . Four resistant and four vulnerable 10 year old trees were selected among 50 trees, based on their P 50 . Stem s amples , taken next to those used to obtain the vulnerability to cavitation curves, were collected and submitted to increasing positive pressures, in order to simulate increasing tension caused by water stress in the xylem . Then the conductive surface of the samples was stained and s canned and the images were analyzed. X ray microdensity profiles were obtained on the same samples. The microdensity profiles of the 2011 ring were analyzed in three parts, earlywood, transition w ood and latewood. The dynamics of embolism propagation was observed separately in these three parts. O ur results showed that the initiation and the propagation of the cavitation follow a discrete trend, with at least two successive initiation events: first cavitation initiate s and propagate s rapidly in the latewood . Then, a second cavitation event begin s and spread s in the earlywood and eventually propagates to the transition wood, which remains the last conductive part in the ring before full embolism. W e observed that resistant to cavitation trees showed lower transition wood density than vulnerable to cavitation trees.